1995
DOI: 10.1093/bja/74.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Arterial pressure control with isoflurane using fuzzy logic

Abstract: Arterial pressure is still one of the most important measures in estimating the required dose of inhaled anaesthetics. It is measured easily and reacts rapidly which makes it suitable as a variable for feedback control of depth of anaesthesia. Fuzzy logic, a novel approach to feedback control, was used to control arterial pressure in 10 patients during intraabdominal surgery by automatic adjustment of the concentration of isoflurane in fresh gas. During anaesthesia, fuzzy control periods of 45-min duration wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…As a case study, in this paper, a fuzzy logic controller is deployed to measure the MAP [21,22]. This controller simulates the relationship between the inflow concentration of Isoflurane, and the blood pressure.…”
Section: Lemma 23mentioning
confidence: 99%
“…As a case study, in this paper, a fuzzy logic controller is deployed to measure the MAP [21,22]. This controller simulates the relationship between the inflow concentration of Isoflurane, and the blood pressure.…”
Section: Lemma 23mentioning
confidence: 99%
“…The use of plasma or effect-site targeted drug administration is well understood and will lower the order of complexity of the resulting system [30]. Nowadays, the use of modern powerful microprocessors may allow better control through the incorporation of more sophisticated models describing the dose-response relationship, or by reverting to other control algorithms like MPC or fuzzy logic [31,32].…”
Section: Control Methodsmentioning
confidence: 99%
“…Various theoretical approaches can be used to adapt the control parameters toward the behavior characteristics of a specific individual. Examples are state estimation, mixed-effects pharmacokinetic or dynamic modeling using Bayesian estimation [33 • , 34], Kalman filtering [35], fuzzy logic [31,36] or other engineering techniques such as neural network applications [37] and reinforced learning [38,39]. Bayesian optimization, as proposed by Sheiner and coworkers [40], individualizes the pharmacodynamic relationship by combining individual information with the knowledge of an a priori probability density function containing the statistical properties of the parameter to be estimated [41].…”
Section: Control Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It soon became clear that control of anesthesia poses a manifold of challenges, with multivariable characteristics (Zbinden et al;1995), time delay between drug administration and the clinical effect which can lead to system oscillations , different dynamics depending on anesthetics substances (Absalom and Struys; and stability problems (Asbury;1997). Further investigations proved Propofol to be an anesthetic tackled well in control problems (Kenny and Mantzaridis;, while recent studies showed that the control performance may also depend on the controlled variable (Ting et al;.…”
Section: Introductionmentioning
confidence: 99%